2018
DOI: 10.1007/s00203-018-1483-5
|View full text |Cite
|
Sign up to set email alerts
|

Polynucleotide phosphorylase is involved in the control of lipopeptide fengycin production in Bacillus subtilis

Abstract: Bacillus subtilis is a wealth source of lipopeptide molecules such as iturins, surfactins and fengycins or plipastatins endowed with a range of biological activities. These molecules, designated secondary metabolites, are synthesized via non-ribosomal peptides synthesis (NRPS) machinery and are most often subjected to a complex regulation with involvement of several regulatory factors. To gain novel insights on mechanism regulating fengycin production, we investigated the effect of the fascinating polynucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
3
21
0
1
Order By: Relevance
“…Another aim of this study was to construct a strain that ensures constitutive plipastatin mono-production. In a recent work, it was shown that deletion of srfAA signi cantly reduces the plipastatin production and on the other hand deletion of srfAC showed no effect [23]. The authors argued that probably srfAA and comS have a regulatory effect on fengycin production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another aim of this study was to construct a strain that ensures constitutive plipastatin mono-production. In a recent work, it was shown that deletion of srfAA signi cantly reduces the plipastatin production and on the other hand deletion of srfAC showed no effect [23]. The authors argued that probably srfAA and comS have a regulatory effect on fengycin production.…”
Section: Discussionmentioning
confidence: 99%
“…encode for more than one lipopeptide synthetase, which are not synthesized simultaneously in the same growth phase showing the involvement of different regulators. More speci cally, in the genome of bacteria that have the ppsABCDE operon, the srfAA-AD operon is always present as well [22,23]. However, while surfactin is being produced in the late exponential phase, the biosynthesis of plipastatin has been characterized in the stationary phase [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…encode for more than one lipopeptide synthetase, which are not synthesized simultaneously in the same growth phase showing the involvement of different regulators. More speci cally, in the genome of bacteria that have the ppsABCDE operon, the srfAA-AD operon is always present as well [24,25]. However, while surfactin is being produced in the late exponential phase, the biosynthesis of plipastatin has been characterized in the stationary phase [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…More speci cally, in the genome of bacteria that have the ppsABCDE operon, the srfAA-AD operon is always present as well [24,25]. However, while surfactin is being produced in the late exponential phase, the biosynthesis of plipastatin has been characterized in the stationary phase [25][26][27]. Lipopeptide synthetases are usually regulated by complex regulatory networks in a growth-phase dependent manner.…”
Section: Introductionmentioning
confidence: 99%